The Relationship of Knowledge Level and Attitude of Kahean Women on the Use of Hazardous Facial Whitening Cream - Arsiaty Sumule (PT Inovasi Pratama Internasional, 2022)
One of the most widely used cosmetic preparations by Indonesian women is facial whitening products. Wanting to have white and smooth facial skin is a natural thing for women. This makes them do various ways to get white and smooth skin, one of which is by using facial whitening products. The purpose of this study was to determine the relationship between the level of knowledge and attitudes of women in Kahean Village towards the use of dangerous face whitening creams. This research uses descriptive research method with cross sectional design. The sample of this study were women in Kahean Village aged 17-50 years as many as 80 respondents, by filling out a questionnaire containing knowledge and attitude questions then the data were processed using chi square analysis with a 95% confidence level using the SPSS program. The results of this study indicate that the knowledge of women in Kahean Village on the use of harmful face whitening products in the good category is 61%, the sufficient category is 2%, the less category is 21%, the bad category is 16%. Women's attitudes are included in the good category as much as 37%, enough category 27%, less category 36%. From the results of the study, it was concluded that there was a significant relationship between the level of knowledge and attitudes towards the selection of harmful facial whitening products with a p-value of 0.000 (<0.05).